Comparative effectiveness and acceptability of HIF prolyl-hydroxylase inhibitors versus for anemia patients with chronic kidney disease undergoing dialysis: a systematic review and network meta-analysis - Qiong Huang; Qiong Huang; Minling You; Weijuan Huang; Jian Chen; Qinming Zeng; Longfeng Jiang; Xiuben Du; Xusheng Liu; Ming Hong; Jing Wang (Frontiers Media S.A., 2023)
Background: The comparative benefits and acceptability of HIF-PHIs for treating anemia have not been well researched to date. We sought to compare the effectiveness of 6 HIF-PHIs and 3 ESAs for the treatment of renal anemia patients undergoing dialysis.Data sources: Cochrane Central Register of Controlled Trials, PubMed, Embase, Cochrane Library, MEDLINE, Web of Science, and clinicaltrials.gov databases.Results: Twenty-five RCTs (involving 17,204 participants) were included, all of which were designed to achieve target Hb levels by adjusting thee dose of HIF-PHIs. Regarding the efficacy in achieving target Hb levels, no significant differences were found between HIF-PHIs and ESAs in Hb response at the dose-adjusted designed RCTs selected for comparison. Intervention with roxadustat showed a significantly lower risk of RBC transfusion than rhEPO, with an OR and 95% CI of 0.76 (0.56-0.93). Roxadustat and vadadustat had higher risks of increasing the discontinuation rate than ESAs; the former had ORs and 95% CIs of 1.58 (95% CI: 1.21-2.06) for rhEPO, 1.66 (1.16-2.38) for DPO (darbepoetin alfa), and 1.76 (1.70-4.49) for MPG-EPO, and the latter had ORs and 95% CIs of 1.71 (1.09-2.67) for rhEPO, 1.79 (1.29-2.49) for DPO, and 2.97 (1.62-5.46) for MPG-EPO. No differences were observed in the AEs and SAEs among patients who received the studied drugs. Results of a meta-analysis of gastrointestinal disorders among AEs revealed that vadadustat was less effect on causing diarrea than DPO, with an OR of 0.97 (95% CI, 0.9-0.99). Included HIF-PHIs, were proven to be more effective than ESAs in reducing hepcidin levels and increasing TIBC and serum iron level with OR of −0.17 (95% CI, −0.21 to −0.12), OR of 0.79 (95% CI, 0.63-0.95), and OR of 0.39 (95% CI, 0.33-0.45), respectively.Conclusion: HIF-PHIs and ESAs have their characteristics and advantages in treating anemia undergoing dialysis. With the selected dose-adjusted mode, some HIF-PHIs appeared to be a potential treatment for DD-CKD patients when ompared with rhEPO, due to its effectiveness in decreasing the risk of RBC transfusion rate or regulating iron or lipid metabolism while achieving target Hb levels.Systematic Review Registration:https://www.crd.york.ac.uk/PROSPERO/display_record.php?RecordID=306511; Identifier: CRD42022306511